MICROPLASTIC REMOVAL IN WASTEWATER USING HORIZONTAL SUBSURFACE CONSTRUCTED WETLAND - Setiadewi, Nurul
Waste Water Treatment Plant (WWTP) has the potential to reduce the amount of microplastic. The concentration of microplastics in the inlet of urban scale WWTP ranged from 15,45 - 17,1 particles/liter, while at the residential scale was 434,67 - 973,33 particles/liter. Microplastics were still found in the urban scale WWTP effluent with a concentration range of 7,1 - 8,25 particles/liter, while at the residential scale was 81,67 - 203,67 particles/liter. This still potentially pollute the environment, so it needs further processing. Constructed Wetland (CW) has the potentially used to increase the removal efficiency of microplastics presented in wastewater from domestic WWTP effluent. This study aims to analyze the efficiency of microplastic removal in wastewater using constructed wetlands. The research was conducted on a laboratory scale using a horizontal subsurface constructed wetland reactor, planted by Vetiveria zizanioides. The research variations tested included microplastic concentrations (80, 120, 200 particles/liter), media (sand and gravel), and hydraulic retention time (HRT 1 day and 4 days). The results showed that microplastics were not detected in the treated water effluent in each treatment tested, so that the efficiency of removing microplastics in wastewater using horizontal subsurface constructed wetlands reached 100%. This indicates that microplastics are fully retained in the constructed wetland treatment system. However, the horizontal distribution of microplastics in wastewater indicated that there was a decrease in concentration from the inlet to the outlet. Research variations of sand media planted by Vetiveria with 4 days HRT showed better removal, The distribution distance of microplastics in wastewater was 15-20 cm from the inlet and the amount obtained was 16.22%, dominantly of polyester (PES). The characteristics of microplastics can affect their fate and transport. The coefficient of microplastic removal rate (k) was determined by using first order kinetic, which resulted the value of k was 0.115 - 0.161/day for a concentration of 80 particles/liter, 0.083 - 0.167/day for a concentration of 120 particles/liter, and 0.128 - 0.157/ days for a concentration of 200 particles/liter. Meanwhile, for the COD parameter, k values were obtained between 0.034 - 0.085/day, Total Nitrogen (TN) parameter between 0.022 - 0.057/day and Total Phosphorus (TP) parameter between 0.020 - 0.060/day.